2022
DOI: 10.1371/journal.pone.0274350
|View full text |Cite
|
Sign up to set email alerts
|

Association between inflammatory biomarkers and cognitive aging

Abstract: Inflammatory cytokines and chemokines related to the innate and adaptive immune system have been linked to neuroinflammation in Alzheimer’s Disease, dementia, and cognitive disorders. We examined the association of 11 plasma proteins (CD14, CD163, CD5L, CD56, CD40L, CXCL16, SDF1, DPP4, SGP130, sRAGE, and MPO) related to immune and inflammatory responses with measures of cognitive function, brain MRI and dementia risk. We identified Framingham Heart Study Offspring participants who underwent neuropsychological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 72 publications
(83 reference statements)
0
12
0
Order By: Relevance
“…sCD14 is negatively related to brain volumes in people with irritable bowel syndrome (IBS) (Weaver et al., 2016), supporting the idea that increased bacterial translocation negatively affects brain volume. Similarly, recent studies in elderly found that high levels sCD14 and other inflammatory markers are correlated to low brain volume, impaired cognition and incident dementia (Fang et al., 2022; Pase et al., 2020).…”
Section: Introductionmentioning
confidence: 83%
“…sCD14 is negatively related to brain volumes in people with irritable bowel syndrome (IBS) (Weaver et al., 2016), supporting the idea that increased bacterial translocation negatively affects brain volume. Similarly, recent studies in elderly found that high levels sCD14 and other inflammatory markers are correlated to low brain volume, impaired cognition and incident dementia (Fang et al., 2022; Pase et al., 2020).…”
Section: Introductionmentioning
confidence: 83%
“…Our primary analyses focused on the three cognitive domain factor (2) CVD risk factors including systolic and diastolic blood pressures (mmHg), diabetes status, treatment for hypertension, body mass index (kg/m 2 ), current smoking status, total cholesterol level (mg/ dL), high-density lipoprotein cholesterol levels (HDL, measured in mg/dL), and use of lipid-lowering agents at Exam 7 Fang, Doyle, Chen, et al, 2022). Diabetes status was defined by whether any of the following was satisfied: use of antidiabetic medications, fasting blood glucose level ≥126 mg/dL, or random blood glucose level ≥198 mg/dL.…”
Section: Association Of Np Cognitive Scores With Inflammatory Proteinsmentioning
confidence: 99%
“…and myeloperoxidase (MPO) were associated with poor performance in NP tests regarding executive function (Fang, Doyle, Chen, et al, 2022). It only assessed APOE ε4 carrier status and individual NP tests rather than the cognitive factor scores in the three APOE strata.…”
Section: Deficits In Executive Function Have Been Observed In Personsmentioning
confidence: 99%
“…Other polyphenolic compounds, including ss-caryophyllene and carnosic acid, and camellia oil were also demonstrated to show anti-inflammatory activity and thus act as potential neuroprotective compounds [ 85 , 88 , 89 ]. The RAGE-induced activation of CD5L, an inflammatory protein, leads to the decreased brain volumes, while higher circulating soluble RAGE (s-RAGE), which functions as a decoy receptor for RAGE, was associated with increased brain volumes in AD models [ 90 ]. High mobility group box1 (HMGB1), a nuclear protein, interacts with RAGE, thereby inducing various inflammatory pathways that would lead to neurological diseases, including AD, and cardiovascular diseases [ 20 ].…”
Section: Rage and Gut Microbiotamentioning
confidence: 99%